Propranolol 0.2% Eye Micro-Drops for Retinopathy of Prematurity: A Prospective Phase IIB Study - Filippi, Luca; Cavallaro, Giacomo; Berti, Elettra; Padrini, Letizia; Araimo, Gabriella; Regiroli, Giulia; Raffaeli, Genny; Bozzetti, Valentina; Tagliabue, Paolo; Tomasini, Barbara; Mori, Annalisa; Buonocore, Giuseppe; et al. (Frontiers in Pediatrics, 2019)
Background. Oral propranolol reduces retinopathy of prematurity (ROP) progression, although not safely. Propranolol 0.1% eye micro-drops administered to newborns with stage 2 ROP are well tolerated, but not sufficiently effective. Methods. A multicenter open-label trial was conducted to assess safety and efficacy of propranolol 0.2% eye micro-drops in newborns with stage 1 ROP. The progression of the disease was evaluated with serial ophthalmologic examinations. Hemodynamic, respiratory, biochemical parameters and propranolol plasma levels were monitored. Results. Ninety-eight newborns were enrolled. The progression to ROP stage 2 or 3 plus was significantly lower than the incidence expected on the basis of historical data (Risk Ratio 0.521, 95% CI 0.297-0.916). No adverse effects related to propranolol were observed and the mean propranolol plasma level was significantly lower than the safety cut-off of 20 ng/mL. Unexpectedly, three newborns treated with oral propranolol before the appearance of ROP, showed a ROP unresponsive to propranolol eye micro-drops and required laser photocoagulation treatment. Conclusion. Propranolol 0.2% eye micro-drops reduced ROP progression and were well tolerated. Propranolol administered too early appears to favor a more aggressive ROP, suggesting that β-adrenoreceptor blockade is useful only during the proliferative phase. Further randomised placebo-controlled trials are required to confirm current results.